A human biomonitoring (HBM) Global Registry Framework: further advancement of HBM research following the FAIR principles - Zare Jeddi, Maryam (2021)
Data generated by the rapidly evolving human biomonitoring (HBM) programs are providing invaluable opportunities to support and advance regulatory risk assessment and management of chemicals in occupational and environmental health domains. However, heterogeneity across studies, in terms of design, terminology, biomarker nomenclature, and data formats, limits our capacity to compare and integrate data sets retrospectively (reuse). Registration of HBM studies is common for clinical trials; however, the study designs and resulting data collections cannot be traced easily. We argue that an HBM Global Registry Framework (HBM GRF) could be the solution to several challenges hampering the (re)use of HBM (meta)data. The aim is to develop a global, host-independent HBM registry framework based on the use of harmonized open-access protocol templates from designing, undertaking an HBM study to the use and possible reuse of the resulting HBM (meta)data. This framework should apply FAIR (Findable, Accessible, Interoperable, and Reusable) principles as a core data management strategy to enable the (re)use of HBM (meta)data to its full potential through the data value chain. Moreover, we believe that the implementation of FAIR principles is a fundamental enabler for digital transformation within environmental health. The HBM GRF would encompass internationally harmonized and agreed open access templates for HBM study protocols, structured web-based functionalities to deposit, find, and access harmonized protocols of HBM studies. Registration of HBM studies using the HBM GRF is anticipated to increase the FAIRness of the resulting (meta)data. It is also considered that the harmonization of existing data sets could be performed retrospectively. As a consequence, data wrangling activities to make data ready for analysis will be minimized. In addition, this framework would enable the HBM (inter)national community to trace new HBM studies already in the planning phase and their results once finalized. The HBM GRF could also serve as a platform enhancing communication between scientists, risk assessors, and risk managers/policymakers. The planned European Partnership for the Assessment of Risk from Chemicals (PARC) works along these lines, based on the experience obtained in previous joint European initiatives. Therefore, PARC could very well bring the first demonstration of the first essential functionalities within the development of the HBM GRF.